Usefulness of an in vitro cellular expression model for haemophilia A carrier diagnosis: illustration with five novel mutations in the F8 gene in women with isolated factor VIII:C deficiency. (24th February 2015) - Roualdes, O.; Nougier, C.; Fretigny, M.; Talagrand, E.; Durand, B.; Negrier, C.; Vinciguerra, C.
Summary This study aims to determine the way to predict the haemophilia A (HA) carrier status and the potential severity in six females with low FVIII:C levels (<0.50 IU mL−1), F8 gene variations and without family history of HA. Except p.Ser577Tyr, F8 gene variations that we reported have never been described (p.Leu107His, p.Pro521Leu, p.Val682Leu, p.Leu2032Pro, p.Ala315dup). Prediction of their potential causal impact was studied by two strategies: bioinformatics approaches and site‐directed mutagenesis followed by FVIII cellular expression into COS‐1 cell. FVIII clotting assay (FVIII:C) and antigen (FVIII:Ag) were assayed in vitro. In silico analysis showed the probably damaging effect of all substitutions and the full conservation of the residues across mammalian species, except for p.Leu2032Pro. The in vitro variant expression model showed abnormal intra and/or extracellular FVIII:C and FVIII:Ag levels for five mutations, which suggest their causality in HA and provide informations about the involved mechanism. We suspect a defect in synthesis and secretion for p.Leu107His, p.Ala315dup and p.Pro521Leu. The mutation p.Val682Leu only affects the FVIII function while p.Ser577Tyr alters function and synthesis. The variant p.Leu2032Pro is probably a polymorphism because no alteration of the FVIII protein expression was observed in vitro. In vitro results suggest that mutations p.Ser577Tyr and p.Ala315dup could led to a severe HA in men. This study demonstrates the ability of this in vitro cellular expression model to contribute to the diagnosis strategy for female suspected of being HA carrier, without HA family history and with a novel F8 gene variation and to provide new criteria for the genetic counselling.